The Psychometric Properties of the Norwegian version of The Pediatric Quality of Life Inventory TM, 4.0 (PedsQL TM) - Reinfjell, Trude; Jozefiak, Thomas (PsykTestBarn, 2012)
Description: The Pediatric Quality of Life Inventory TM (PedsQL TM) is a questionnaire measuring quality of life, which was developed by James W. Varni. The questionnaire was published in English in 1999. Trude Reinfjell and Trond H. Diseth translated the questionnaire into Norwegian in 2006. The copyrightholder has approved the translation. The PedsQL TM measures quality of life in children, adolescents and young adults. There are five versions of the PedsQL TM customized for different informants and age groups: young children (ages 5-7), children (ages 8-12), adolescents (ages 13-18), young adults (ages 18-25), and a parent version for toddlers and preschool children (ages 2-4). There are also parent versions for ages 5-7, 8-12, 13-18 and 18-25. Both the child and parent versions of the questionnaire for the age groups 8-12, 13-18 and 18-25 have four subscales with a total of 23 items. The subscales are Physical functioning (eight items), Emotional functioning (five items), Social functioning (five items) and School functioning (five items). A score can be calculated for each subscale. All 23 items produce a total score, where 100 points indicate optimal quality of life. A Psychosocial score can also be calculated (based on the subscales Emotional, Social and School functioning). It takes less than 30 minutes to complete the questionnaire. The test can be scored manually. The SPSS syntax file is available upon request (contact TR). For interpretation of the scores, a 3-year higher education in health or social studies and test-specific training are required. Literature search: Our systematic literature search identified three publications reporting PedsQL TM data in Norwegian samples, and two publications from Swedish samples (PedsQL TM for the age groups 8-12 and 13-18, self and parent report). We did not identify any psychometric evidence for the other PedsQL TM versions. There are no national norms for the PedsQL TM. One Norwegian study reported representative data from the general population from the county of Sør-Trøndelag (ages 13-15) and two of the Norwegian studies reported data from a clinical population (casus control design). Psychometrics: Overall, we found limited documentation for the psychometric properties of the PedsQL TM, except for adolescents aged 13-15. Factor analyses indicate tentative support for a four-factor model. The instrument shows adequate reliability for all subscales (>0.70). Conclusion: The PedsQL TM is a promising instrument for both clinical and research purposes. The psychometric properties were found to be adequate for adolescents aged 13-15. The PedsQL TM is therefore particularly recommended for this age group.